Private Enforcement and Legal Privilege Versus Convergency - Valeria Falce (Market and Competition Law Review)
Directive 2014/104/EU has been implemented also in Italy, thus reinforcing the effectiveness of competition law at national level too. Through a “two point” system, therefore public and private enforcement qualify today for complementary means towards the same end. Within such binary system, different issues and topics have been addressed so far by the academic community: from the binding nature of competition authorties decisions to the introduction of the powerful system of assumptions, to the alleviation of the burden of allegation, to the “passing on” rules, to the new role given to competition authorities in general, etc.. The provision devoted to the legal privilege covering the attorney-client communications, instead, has been almost neglected. In the following, the legal privilege will be analyzed in depth, since, thanks to the implementing provision, it will be able to acquire in Italy a renewed relevance in terms of both legal framework and scope of application.